The role of subarachnoid hemorrhage in post-traumatic Seizures: Insights from a retrospective study on TBI and seizure patterns - Suleiman Daoud; Atef F. Hulliel; Rasha S. Mustafa; Almutazballlah Qablan; Yasmeen Jamal Alabdallat; Sa’ed Hasan; Nataly Al-zubi; Adam M. Abdallah; Mohammad Alsharman; Amer Jaradat; Sultan Jarrar; Mohammad A Jamous (Brain Hemorrhages)
Objective: Traumatic brain injury (TBI) and post-traumatic seizures (PTS) have been interconnected since ancient times. Modern research emphasizes their impact on morbidity and mortality, with persistent seizures linked to poor cognitive outcomes. PTS complicates recovery, especially when early seizures indicate severe injury. This study explores how different TBI types affect the development of focal versus generalized seizures to improve clinical management. Methods: A retrospective study at King Abdullah University Hospital (KAUH), Jordan, examined 1934 TBI cases from 2017 to 2023, identifying 118 patients with confirmed post-traumatic seizures. Results: Among 118 patients, the median age was 21.5 years (range 2–86), and most were male (74.6 %). Trauma types included Intracerebral Hemorrhage (47.5 %), Subarachnoid Hemorrhage (38.1 %), Intraventricular Hemorrhage (17 %), Subdural Hematoma (28.8 %), Epidural Hematoma (12.7 %), and Skull Fractures (38.1 %). Generalized tonic-clonic seizures occurred in 69.5 %, while 30.5 % were focal. At study end, 84.7 % of patients survived. Binary logistic regression revealed that Subarachnoid Hemorrhage (SAH) significantly increased the likelihood of generalized seizures (odds ratio 3.308, p = 0.005). Other trauma types did not significantly affect seizure type. Conclusion: Subarachnoid hemorrhage (SAH) significantly increases the likelihood of generalized tonic-clonic seizures, suggesting it as a key risk factor. Further research is needed to refine preventive and treatment strategies.